Analisis Pengendalian Kualitas Hasil Uji Tarik Material Plat ST 37 Dengan Menggunakan Metode SPC - E P D Boangmanalu; A B Pratama; J F HT Saragi; Sahat (Jurnal MESIL (Mesin Elektro Sipil), 2024)
This research aims to determine the quality of tensile testing from Politeknik Negeri Medan Mechanical Engineering students using specimens from st 37 plate material. The process carried out is testing the material on a tensile testing machine and analyzing the data using the Statistical Process Control (SPC) method, both with formulas and also Minitab software. Based on the tensile test results, variable inspection results were found, namely x ? ? = 347.1489 MPa, UCL = 363.858 MPa and LCL = 330.4939 MPa, from the X-Chart control diagram the 8th test results exceeded the lower control limit or UCL. The results of the tensile test using the R-Chart control diagram found a value of UCL = 61.2202 and LCL = 0, from the control diagram it was not found out of control or still within the control limits. The use of cause and effect diagrams found factors that influenced the tensile test results, namely students who are still beginners, not careful and also don't have the skills, then the factor of machines that are not maintained which affects performance so that it is not precise, then equipment is lacking, then methods for making specimens that do not follow standard operating procedures.